Metabolic, oxidative stress and inflammatory markers in adult women exposed to secondhand smoke - Mohd Hanaffi, Siti Hajar (2015)
Introduction: Secondhand smoke (SHS) is formed from the burning of cigarettes and other tobacco products and from smoke exhaled by smokers. Most of the mortality and morbidity attributable to exposure of adults to SHS is related to cardiovascular diseases. Objectives: This study aims to determine the effects of SHS exposure on metabolic, oxidative stress and inflammatory markers in healthy adult women. Methods: This is a comparative cross-sectional study between the group of selfreported SHS (n=101) and non-SHS exposure (n=91) in healthy women without clinical evidence of cardiovascular disease. Exposure to SHS is defined as exposed to secondhand smoke for at least 15 minutes in 2 days within a week, while non-SHS is people not exposed to SHS. Blood was drawn from all eligible subjects to measure metabolic (High molecular weight (HMW) adiponectin, insulin, homeostasis model assessment (HOMA-IR) and non-estrified fatty acids (NEFA), oxidative stress (oxidized low density lipoprotein (oxidized LDL) and 8-isoprostane) and inflammatory (hsCRP) markers. Hair nicotine analysis was performed to validate the exposure status in subjects. Results: Hair nicotine levels were significantly higher in SHS exposure group compared to non-SHS exposure group [0.22 (0.62) vs. 0.04 (0.11) ng/mg; p=0.009]. No significant differences were observed in HMW adiponectin, insulin and insulin resistance (HOMA-IR), NEFA, 8-isoprostane, oxidized LDL and hsCRP between the two groups, even after controlling for several potential confounders. Serum HMW adiponectin was negatively correlated with insulin level and insulin resistance (HOMA-IR) in the group of women exposed to SHS. No significant correlation was seen between HMW adiponectin and NEFA, 8-isoprostane, oxidized LDL and hsCRP in SHS women. Conclusion: This study did not show any significant differences in metabolic, oxidative stress and inflammatory markers in healthy adult women exposed and nonexposed to SHS. Low serum HWM adiponectin is associated with increased insulin level and resistance in SHS exposed women.